Effect of phosphonium based ionic liquid on structural, electrochemical and thermal behaviour of polymer poly(ethylene oxide) containing salt lithium bis(trifluoromethylsulfonyl)imide. Issue 91 (14th September 2016) - Gupta, Himani; Shalu,; Balo, Liton; Singh, Varun Kumar; Chaurasia, Sujeet Kumar; Singh, Rajendra Kumar
Abstract : Decrement in conductivity and flexibility of polymer electrolytes at higher ionic liquid concentration due to the crowding of anions. Abstract : Solid polymer electrolytes (SPEs) using polymer poly(ethylene oxide) (PEO), lithium salt bis(trifluoromethylsulfonyl)imide (LiTFSI) and ionic liquid (IL) trihexyltetradeylphosphonium bis(trifluoromethylsulfonyl)imide have been prepared. These prepared solid polymer electrolyte films have been characterised by using different experimental techniques: X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermo gravimetric analysis (TGA), complex impedance spectroscopy, Fourier transform infrared spectroscopy (FTIR), an electrochemical analyser etc. Changes in crystallinity, melting temperature ( T m ), glass transition temperature ( T g ), thermal stability and ionic transport behaviour of the prepared polymer electrolyte have been observed when the LiTFSI salt and different concentrations of IL were incorporated in the pristine polymer PEO. Ionic conductivity of the prepared solid polymer electrolyte (PEO + 20 wt% LiTFSI) has been found to increase with increasing IL concentration in polymer electrolytes up to 20 wt% IL. Total ionic transference number >0.99 and cationic transference number ∼0.37 with an electrochemical window of ∼3.34 V has been observed for the optimized solid polymer electrolyte (PEO + 20 wt% LiTFSI + 20 wt% IL). Temperature dependant ionic conductivity obeys Arrhenius type thermally activated behaviour.